The Key Physiological and Biochemical Traits Underlying Common Bean (Phaseolus vulgaris L.) Response to Iron Deficiency, and Related Interrelationships - Khawla Nsiri; Abdelmajid Krouma (Agronomy, 2023)
Iron deficiency is a worldwide nutritional problem affecting crop production. In Tunisia, this mineral disorder hampers the growth and yield of the major crops due to the abundance of calcareous soils that limit iron availability. The common bean is one of these crops suffering from lime-induced iron chlorosis. The exploration of the variability of common bean responses to iron deficiency allows us to screen tolerant cultivars and identify useful traits and indicators for further screening programs. To this end, two common bean cultivars (coco blanc, CB, and coco nain, CN) were cultivated hydroponically in standard nutrient solution (control) or nutrient solution deprived of iron (stressed). Analyses were reported on plant growth, photosynthetic pigments, photosynthesis, iron distribution, H-ATPase, and Fe-chelate reductase (Fe-CR) activities; important indicators were calculated; and convenient correlations were established. Current results demonstrated that iron deficiency stimulated specific symptoms of iron chlorosis on young leaves that were more precocious and severe in CB than CN. Spad index and chlorophyll pigments measurement confirmed these morphological changes and cultivar differences. Net photosynthesis (Pn) showed the same scheme of variation, with a significant decrease in Pn while respecting the previous cultivar’s variability. Plant growth is no exception to this general trend. The biomass decrease was two times higher in CB than CN. Otherwise, this mineral disorder significantly decreased Fe concentration in all plant organs. However, CN accumulated 40% more Fe than CB, resulting from its higher Fe Fe-CR and H-ATPase activities. Our results also demonstrated the close dependence of these metabolic functions on Fe availability in shoots and the strict relationship between Fe-CR and H-ATPase, photosynthesis, and chlorophyll content. Otherwise, CN demonstrated higher efficiency of Fe’s use (FeUE) for the key metabolic functions (photosynthesis, chlorophyll biosynthesis, and plant growth). The relative tolerance of CN as compared to CB was explained by its ability to establish a functional system less vulnerable to iron deficiency that operates effectively under problematic conditions. This system involves metabolic functions in shoots (photosynthesis, chlorophyll biosynthesis, Fe repartition, etc.) and others in roots (H-ATPase, Fe-CR), which are strictly interdependent.